Evaluation of shortness of breath presenting to emergency department of a tertiary care centre - Tiwari, Sanjeeb; Acharya, Saroj; Thapa, Anusha (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Dyspnea, or shortness of breath (SOB), is a common reason for emergency department (ED) visits and is linked with significant morbidity. This study aimed to determine the current prevalence, time of presentation, and common provisional diagnoses of patients presenting with dyspnea at a tertiary care hospital in Nepal. Method: A descriptive cross-sectional study was conducted in the Emergency Department of Tribhuvan University Teaching Hospital, Kathmandu, from Jan to Mar 2024. The study population comprised all emergency department visits during this period (N = 11,260). Using systematic random sampling, every 22nd patient record from all ED admissions was reviewed to reach the calculated sample size of 499. Data on demographics, time of arrival, provisional diagnosis, and disposition were analyzed descriptively. Result: Out of 499 patients, 103 (20.64%; 95% CI: 17.07–24.19) presented with shortness of breath. The median age was 38 years (IQR: 30.5 years); 65(63.11%) were female. Most younger patients arrived in the morning, while older patients presented in the evening. Chronic obstructive pulmonary disease 25(24.27%) and bronchial asthma 24(23.30%) were the most common provisional diagnoses, followed by pneumonia and anxiety. A clear temporal pattern of presentation was noted for certain conditions, such as asthma peaking in the early morning. Conclusion: This research shows that a growing number of emergency department visits are due to dyspnea. This condition affects a younger age group and has a noticeable gender gap, likely caused by indoor air pollution and chronic respiratory illnesses.